2002
DOI: 10.1016/s0736-0266(02)00064-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased content of type III collagen at the rupture site of human Achilles tendon

Abstract: We compared the type 1 and I11 collagen amounts and cross-linked telopeptides at the rupture site and two other sites of the same tendon. Tendon saniples of ten individuals with total Achilles tendon rupture and six healthy cadavers were collected. The newly synthesized type I and 111 procollagens were assessed by extracting the soluble propeptides PINP, PICP and PIIINP. The insoluble matrix was solubilized by heat denaturation and trypsin digestion. Hydroxyproline, the cross-linked telopeptide structures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(129 citation statements)
references
References 23 publications
13
112
1
1
Order By: Relevance
“…These data are consistent with the hypothesis that increased matrix turnover is associated with the sub-clinical matrix degeneration that precedes the clinical condition. Similar biochemical evidence now exists for the Achilles, suggesting that remodelling of the tendon is a general feature of tendinopathy (Eriksen et al, 2002). Whether this remodelling weakens the tendon is a moot point, since many cases of painful tendinopathy persist for months if not years, and do not go on to rupture.…”
Section: The Biochemistry Of Tendinopathymentioning
confidence: 66%
“…These data are consistent with the hypothesis that increased matrix turnover is associated with the sub-clinical matrix degeneration that precedes the clinical condition. Similar biochemical evidence now exists for the Achilles, suggesting that remodelling of the tendon is a general feature of tendinopathy (Eriksen et al, 2002). Whether this remodelling weakens the tendon is a moot point, since many cases of painful tendinopathy persist for months if not years, and do not go on to rupture.…”
Section: The Biochemistry Of Tendinopathymentioning
confidence: 66%
“…Collagen protein typing of injured tendons has shown that type-III collagen can increase up to 15% of total collagen content following injury 43 . Collagen fibers have been found to be not only smaller in diameter but also structurally weaker to tensional forces when type-III content is higher 43,50,51 . Consequently, the type-III to type-I collagen expression ratio is an ideal dynamic indicator of tendon injury response and also provides an important insight into the functional strength and resiliency of the tendon.…”
Section: Type-iii To Type-i Collagen Expression Ratiomentioning
confidence: 99%
“…Additionally, the information gained from this acute injury model may provide insight into chronic injury responses. Investigators have demonstrated that elevated levels of type-III collagen are present in chronic tendinopathies and degenerative tendon tears as well 30,43,50 .…”
Section: Type-iii To Type-i Collagen Expression Ratiomentioning
confidence: 99%
“…For example, thickening of Achilles tendon is a precursor tendon ruptures. [7][8][9][10] To determine the pathological changes for the size of Achilles tendon, it is necessary to to know the normal size. In this study, we aimed to reveal the normal morphometric values of Effects of physical characteristics, exercise and smoking on morphometry of human Achilles tendon: an ultrasound study*…”
Section: Introductionmentioning
confidence: 99%